2009
DOI: 10.1186/1755-8794-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of the human adipose transcriptome and the link to metabolic disease

Abstract: Background: Circadian (diurnal) rhythm is an integral part of the physiology of the body; specifically, sleep, feeding behavior and metabolism are tightly linked to the light-dark cycle dictated by earth's rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 53 publications
10
64
0
Order By: Relevance
“…[19][20][21][22][23][24] In line with this, several hundreds of genes display a diurnal expression rhythm in the adipose tissue of rodent 4,17,25,26 and human, 21 some of which are involved in core adipose functions such as lipolysis, adipogenesis, and metabolic inflammation (detailed genes are specified in Figure 2). 18,21,25 The role of the circadian clock machinery in adipocyte physiology has been described in both in vitro and in animal studies. Knockdown of the clock genes, either Bmal1 or Rev-Erbα, in cells inhibits adipocyte differentiation while mutations of two other clock components, Per2 or retinoid orphan receptor α (RORα), increase adipogenesis.…”
Section: Adipose Tissue Circadian Clocksmentioning
confidence: 97%
See 1 more Smart Citation
“…[19][20][21][22][23][24] In line with this, several hundreds of genes display a diurnal expression rhythm in the adipose tissue of rodent 4,17,25,26 and human, 21 some of which are involved in core adipose functions such as lipolysis, adipogenesis, and metabolic inflammation (detailed genes are specified in Figure 2). 18,21,25 The role of the circadian clock machinery in adipocyte physiology has been described in both in vitro and in animal studies. Knockdown of the clock genes, either Bmal1 or Rev-Erbα, in cells inhibits adipocyte differentiation while mutations of two other clock components, Per2 or retinoid orphan receptor α (RORα), increase adipogenesis.…”
Section: Adipose Tissue Circadian Clocksmentioning
confidence: 97%
“…21 Furthermore, diurnal oscillations of serum IL-6 are well documented in humans, 127,128 but the situation is less clear in rodents. 125,126,95 To which extent these adipose-derived cytokine oscillations contribute to metabolic inflammatory processes (see the following text) remains to be explored.…”
Section: Adipokine Rhythmsmentioning
confidence: 99%
“…In addition, SCN-lesion studies showed this variation in endocrine responses to be dependent on a functional SCN (41) . Although it is clear that the SCN plays a key role in the regulation of glucose metabolism, circadian oscillators are not only localised in the SCN, but also in other brain regions and peripheral tissues involved in energy metabolism, including the pancreas (57) , gut (58)(59)(60) , liver (61)(62)(63) , skeletal muscle (64) and adipose tissue (65)(66)(67)(68) . Peripheral clocks do not receive light input directly, but are synchronised by the SCN.…”
Section: Suprachiasmatic Nuclei Regulates Food Intake and Glucose Metmentioning
confidence: 99%
“…20,21 Moreover, use of microarrays suggests that up of 20% of the murine and the human adipose transcriptome is expressed according to diurnal rhythm]. 21,23 Therefore, a recent study performed by our group of research has provided an overall view of the internal tem poral order of circadian rhythms in human adipose tissue represented in a phase map. 24 The data included va rious genes implicated in metabolic processes such as energy intake and expenditure, insulin resistance, adipocyte differentiation, dyslipidemia, and body fat distribution, and indicated that circadian rhythmicity of the genes studied followed a predictable physiological pattern, particularly for subcutaneous depot.…”
Section: Adipose Tissue Changes During the Daymentioning
confidence: 99%